Combating Overweight and Obesity among School Children and Adolescents through Student Counselling in Saudi Arabia - Alotaibi, Turki (European Journal of Social Science Education and Research, 2025)
Overweight and obesity are health problems that can affect many children and adolescents around the world. The literature has identified that the prevalence of overweight and obesity is high in the Kingdom of Saudi Arabia (Saudi Arabia) in children and adolescents attending schools in Saudi Arabia. Student counselling practices can be a cost effective way to help students to deal with overweight and obesity in Saudi schools. The aim of the study was to conduct an evidence-based review of the literature in order to suggest new approaches to applying student counselling services and programmes in order to directly combat overweight and obesity in schools in Saudi Arabia. The study used a non-empirical review of the literature on overweigh and obesity and on student counselling in the United Kingdom and Saudi Arabia. The study argues that in theory student counsellors in schools in Saudi Arabia are ideally placed to help to directly address and reduce the existing high prevalence of overweight and obesity in youths and adolescents attending schools in Saudi Arabia. This could be done using a combination of dietary interventions and counselling methods. The research study concludes that student counselling in schools in Saudi Arabia could potentially be used to directly help to combat and reduce levels of overweight and obesity among school children and adolescents in the long term.
Keywords: Student counselling; overweight; obesity; children; psychotherapy; behavioural therapy; cognitive therapy; health; diet; schools; Saudi Arabia.